Groundwater Vulnerability Analysis in the Cikao Sub-Watershed, Jatiluhur, Purwakarta: A Critical Study for Resource Management - Barkah, Mochamad Nursiyam; Listiawan, Yudhi; Waliyana, T. Yan; Hadian, Mohamad Sapari Dwi; Sulaksana, Nana; ., Hendarmawan (Journal of Ecohumanism, 2025)
An area’s development leads to a rise in its population. The need for clean water also rises as a result of this population growth. The quality of groundwater, one of the community’s clean water sources, is determined by subsurface conditions. The goal of the study is to determine how much the Cikao sub-watershed is impacted by the degree of groundwater vulnerability. It also seeks to ascertain its relationship to the distribution of contaminated groundwater in the same region. East of Purwakarta Regency’s Jatiluhur Reservoir sits the Cikao sub-watershed. The Citarum watershed includes this sub-watershed. The quality of groundwater might deteriorate due to contamination. The DRASTIC approach was used in this investigation. Seven parameters are used in this approach. Direct measurements in main data and indirect measures in secondary data yield the seven parameters. Following processing and analysis, the measurement results are displayed as a thematic map. After that, a map of groundwater vulnerability is superimposed with the seven parameters. The Cikao sub-watershed has three categories of vulnerability, according to the findings of the DRASTIC method analysis: Medium Low (9.76%), Medium High (71.56%), and High (18.68%). The slope and the distance to the depth of the groundwater table are the main determinants of the degree of vulnerability in the Cikao Sub-watershed. According to the findings of the groundwater chemistry test, every sample examined remained within the safe threshold. The iron (Fe) and Nitrate (NO3) elements in the low medium susceptibility zone have the highest levels of content compared to the high susceptibility zone. Please pay attention to vulnerability zones for further regional development, especially the distance from the surface to the groundwater table and the slope.